Influence of cyclosporin A on quality of bone around integrated dental implants: a radiographic study in rabbits - Sakakura, Celso Eduardo; Marcantonio, Elcio; Wenzel, Ann; Scaf, Gulnara [UNESP] (Blackwell Publishing, 2007)
To evaluate the influence of cyclosporin A (CsA) administration on bone around integrated dental implants assessed by a bone quality index and by quantitative subtraction radiography.A total of 36 machine surface commercial implants were placed in 18 adult rabbits. After a 3-month healing period without any disturbance, the animals were randomly divided into three groups of six animals each. Group A was sacrificed at this time. CsA was injected subcutaneously in an immunosuppressive dose of 10 mg/kg/day in a test group (Group T), and a Group B served as a control, receiving only vehicle. After 3 months of cyclosporin administration, the animals of both Groups B and T were sacrificed. Radiographs were obtained at implant surgery and at the day of sacrifice with a CMOS sensor. Bone quality around the implants was compared between the groups using a bone quality index and quantitative subtraction radiography.The bone analysis showed that in Group T, the bone quality changed dramatically from a dense cortical to a loose trabecular bone structure (P < 0.0001, chi(2) test) while in Groups A and B there were no significant differences. Quantitative digital subtraction radiography showed significantly (P < 0.05) lower gray shade values (radiographic density) in a region of bone formation around the implants in Group T (118 +/- 12) than in Groups A (161 +/- 6) and B (186 +/- 10).Within the limits of this study, CsA administration has a negative effect on the quality of bone around integrated dental implant.
Keywords: bone density; cyclosporin; subtraction radiograph; titanium implants